Efektivitas Penggunaan Komik Matematika Dalam Mengenalkan Pembelajaran Matematika Anak Usia 4-5 Tahun Di Taman Kanak-Kanak - Ravel Darma Putra; Dadan Surayana (Universitas Negeri Padang, 2022)
This study aims to determine the effectiveness of the use of math comics in introducing mathematics learning to children aged 4-5 years at the Al Jannah Nanggalo Kindergarten Tarusan, South Coast District. This study linked 20 children as the research object, where 10 people entered the experimental class and 10 were the control class. The research design was a pre-test post-test control group. Collection using a scale, to test the quality of the measuring instrument used content validity test with professional judgement on the contrary to see the reliability using the help of SPSS 15.0 for windows with Alpha Crombach technique. Hypothesis testing uses the statistical technique T-test with the help of SPSS 15.0 for windows which shows a significant level of 0,000. This shows that the use of math is effective for the introduction of mathematics for children aged 4-5 years in kindergarten